2013
DOI: 10.1152/ajpcell.00227.2012
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the orexinergic/hypocretinergic system: a revisit in 2012

Abstract: The neuropeptides orexins and their G protein-coupled receptors, OX(1) and OX(2), were discovered in 1998, and since then, their role has been investigated in many functions mediated by the central nervous system, including sleep and wakefulness, appetite/metabolism, stress response, reward/addiction, and analgesia. Orexins also have peripheral actions of less clear physiological significance still. Cellular responses to the orexin receptor activity are highly diverse. The receptors couple to at least three fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 419 publications
(621 reference statements)
2
140
0
Order By: Relevance
“…Neuropeptides orexin-A and -B are best known for their roles in the regulation of sleep/wakefulness and appetite, but many other prominent functions have also been described (reviewed in Aston-Jones et al, 2010;Scammell and Winrow, 2011;Kukkonen, 2013;Perez-Leighton et al, 2012). Orexins mediate their actions via rhodopsin family G-protein-coupled receptors (GPCRs) named OX 1 and OX 2 , which can be found in the central nervous system (CNS) but also in other parts of the body (reviewed in Scammell and Winrow, 2011;Kukkonen, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptides orexin-A and -B are best known for their roles in the regulation of sleep/wakefulness and appetite, but many other prominent functions have also been described (reviewed in Aston-Jones et al, 2010;Scammell and Winrow, 2011;Kukkonen, 2013;Perez-Leighton et al, 2012). Orexins mediate their actions via rhodopsin family G-protein-coupled receptors (GPCRs) named OX 1 and OX 2 , which can be found in the central nervous system (CNS) but also in other parts of the body (reviewed in Scammell and Winrow, 2011;Kukkonen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Orexins mediate their actions via rhodopsin family G-protein-coupled receptors (GPCRs) named OX 1 and OX 2 , which can be found in the central nervous system (CNS) but also in other parts of the body (reviewed in Scammell and Winrow, 2011;Kukkonen, 2013). Orexin receptor activation leads to signaling via multiple intracellular pathways (reviewed in Kukkonen, 2013). In neurons, activation of orexin receptors usually leads to depolarization through inhibition of K 1 channels or activation of nonspecific cation channels (reviewed in Kukkonen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, two-way ANOVA calculated for AUC values (days [7][8][9][10][11][12] showed an interaction between hole and genotype (F (1,32) =5.05, p<0.05) ( Figure 3C). …”
Section: Hypocretin Receptor-1 Gene Deletion Impairs Win55212-2 Selfmentioning
confidence: 99%
“…The hypocretin system has been reported to play an important role in the reward circuits and to participate in the reinforcing properties of psychostimulants, nicotine, opioids and alcohol (8,9). Several reports have described the existence of functional interactions between the hypocretin and the endocannabinoid systems, mainly in the regulation of appetite and analgesia (10). However, whether hypocretins 4 take part of the neurobiological substrate underlying the addictive properties of cannabinoids remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, glutamatergic fibers make contact with orexin/hypocretin (ORX)-containing neurons in the lateral hypothalamus (Henny & Jones 2006) where these neurons regulate many physiological functions such as the sleep/wake cycle, feeding, and learning and reward processes (Kukkonen 2012). In this context, a recent study suggested a major role of iGluRs and ORX interactions since it has been shown that glutamate agonists initiate excitatory postsynaptic currents by increasing the number of c-Fos-positive hypothalamic ORX neurons (Eyigor et al 2012) as well as ORX-A-dependent anxiety-like behaviors in the bed nucleus of the stria terminalis (Lungwitz et al 2012).…”
Section: Introductionmentioning
confidence: 99%